Sustainable production of nucleoside analogues by a high-efficient purine 2′- deoxyribosyltransferase immobilized onto Ni2+ chelate magnetic microparticles (2019)
The present work aims to develop a magnetic biocatalyst for customized production of nucleoside analogues using mutant His-tagged purine 2′-deoxyribosyltransferase from Trypanosoma brucei (TbPDTV11S) immobilized onto Ni2+ chelate magnetic iron oxide porous microparticles (MTbPDTV11S). Biochemical characterization revealed MTbPDTV11S5 as optimal candidate for further studies (10,552 IU g−1; retained activity 54% at 50 °C and pH 6.5). Interestingly, MTbPDTV11S5 displayed the highest activity value described up to date for an immobilized NDT. Moreover, MTbPDTV11S5 was successfully employed in the one-pot, one-step production of different therapeutic nucleoside analogues, such as cladribine or 2′-deoxy-2-fluoroadenosine, among others. Finally, MTbPDTV11S5 proved to be stable when stored at 50 °C for 8 h and pH 6.0 and reusable up to 10 times without negligible loss of activity in the enzymatic production of the antitumor prodrug 2′-deoxy-2-fluoroadenosine.